Popular education in the 21st century. intercultural resistance from the south and from below - Mejía Jiménez, Marco Raúl (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The way to understand the political, social, cultural, and economic reality of Latin America is still pervaded by West ideas. A project developed from within is required in order to build fairer and more equitable societies in this continent’s wide cultural diversity. Popular education is shown as an alternative to create an educational-political model which vindicates Amerindian populations. Based on the features of South American societies, popular education aims to create a project from the south to propose a different way of understanding Latin American current situation, away from the classical Eurocentric explanations.